Mechanisms of Green Financial Product Innovation in Driving the Low-Carbon Economy: A Systemic Study - Zhang, Qinghua (Simen Owen Academic Proceedings Series, 2025)
The global transition toward a low-carbon economy requires innovative financial instruments to bridge the funding gap for sustainable development. Although green financial products have rapidly proliferated, their systemic mechanisms for facilitating decarbonization remain insufficiently explored. This study examines how innovation in green financial products structurally supports low-carbon transitions through integrated policy, market, and technology interactions. A tripartite mechanism framework is developed, encompassing price discovery, risk allocation, and value circulation, addressing the critical disconnect between financial design and emission-reduction outcomes. Methodologically, the research combines systematic case studies of representative green financial instruments across China, the EU, and the US with a novel mechanism effectiveness assessment matrix, evaluating coverage breadth, market responsiveness, and sustainability impact across twelve flagship products. Findings highlight three key dynamics: policy signals amplify market expectations through certification systems, securitization techniques reduce technology adoption risks, and blockchain-enabled carbon tracing generates positive feedback loops. Products incorporating dynamic ESG pricing demonstrate 23% higher capital efficiency compared with conventional green instruments. This study advances sustainable finance theory by operationalizing the concept of "mechanism stacking," where complementary designs produce nonlinear climate benefits. Practically, it offers regulators evidence-based templates for product standardization and guides financial institutions in designing next-generation climate-aligned instruments. These insights promote the alignment of financial innovation with Paris Agreement targets and emphasize the importance of cross-border mechanism interoperability.